Kānsưksā chapho̜ karanī - Čhin Rakkāndī; Prasongsukkari (Sombun), Khun, 1901-1953 (Krung Thēp : Khrō̜pkhrūa Khun Prasongsukkārī, 1968)
Cremation volume for Khun Prasongsukkari (Sombun Lapcharoen), 1901-1953, former Thai senior official at Ministry of Interior; includes brief biography, condolences.
Keywords: Prasongsukkari -- Khun, -- 1901-1953 -- Death and burial; Thailand. -- Krasūang Mahātthai -- Officials and employees -- Biography; Thailand -- Miscellanea